Lactational exposure of human infants to metal(loid)s in Sub-Saharan Africa and Mediterranean Europe: A systematic review and meta-analysis - Amarachi Paschaline Onyena; Onyinyechi Bede-Ojimadu; Taagbara Jolly Abaate; Dokuboba Amachree; Chiara Frazzoli; Opeyemi M. Folorunso; Beatrice Bocca; Orish E. Orisakwe (Current Research in Toxicology)
Breast milk, a fundamental component of infant nutrition, may serve as a reservoir for various metal(loid)s, which could pose significant health risks to infants of mothers exposed to toxic metals. Human exposure levels to metal(loid)s vary across regions, influenced by differences in diet, lifestyle, and environmental factors. This systematic review compares metal(loid) concentrations in breast milk from Sub-Saharan Africa (SSA) and Mediterranean Europe (Med. Europe), identifying key determinants of exposure. PubMed, Scopus, and Google Scholar were searched for articles reporting metal concentrations in human breast milk samples from SSA and Med. Europe. Weighted mean concentrations were estimated and compared between the two regions. Twenty-five studies from SSA and seventeen from Med. Europe were included in the review. Mean concentrations of cadmium (12.38 ± 1.21 µg/L vs 0.22 ± 0.51 µg/L; p < 0.0001), lead (14.96 ± 8.10 µg/L vs 1.16 ± 4.00 µg/L; p < 0.0001), and mercury (2.01 ± 1.37 µg/L vs 0.95 ± 4.32 µg/L; p = 0.008) were higher in breast milk samples from SSA than Med. Europe. Conversely, breast milk samples from SSA had lower concentrations of selenium (7.38 ± 2.67 µg/L vs 13.09 ± 16.89 µg/L; p < 0.0001) and iron (138.78 ± 106.33 µg/L vs 371.97 ± 446.74 µg/L; p < 0.0001) than those from Med. Europe. Key determinants of metal(loid)s levels in breast milk included maternal smoking, dietary patterns, and environmental exposure. There is an urgent need for effective interventions and policies to reduce metals exposure, particularly in SSA, to safeguard maternal and infant health.